An Evaluation Model for Monitoring Human Resources in the Health System of Iran - MH Mehrolhassani; MR Amiresmaili; M Iranmanesh (مجله اپیدمیولوژی ایران, 2019)
Background and Objectives: Human resources is a key factor in achieving the Millennium Development Goals. Lack of indicators and standard tools for monitoring and evaluating human resources may cause limitations in achieving these goals. This study was done to develop evaluation indicators of human resources in the health sector. Methods: The present study was carried out using the Delphi technique to extract the indicators of human resources evaluation in 2017. To conduct this study, three independent stages including a review of theoretical concepts, preparation of initial indicators of human resources evaluation, and consensus building were undertaken. The data were collected by a panel of 12 experts and representatives of related organizations in three rounds, with a scorecard designed to score from 1 to 10. In each round, the indexes that attained at least 8 out of 10 by two thirds of the experts were confirmed in the final model. Results: In the first stage, 220 indicators were identified. The final model of human resources evaluation had 45 indicators in 11 main criteria. Four criteria were accepted at the stage of entrance to job market, (qualified applicants for health education, accreditation, capacity and outsourcing of health education institutions, approval and licensing). Five criteria were confirmed during the work (main indicators of availability and distribution, activity, productivity of labor force, waste and renewal, desirable governance on the information system of labor). Two criteria were accepted at the exit stage (transfer and withdrawal). Conclusion: Despite the complexity of the human resources assessment, three different stages of the life cycle of the workforce (input, active labor force and output) should be considered for evaluation and monitoring. The indicators presented in this study make it possible to assess and monitor the health workforce.